Nanos suppresses somatic cell fate in Drosophila germ line - Hayashi, Yoshiki (National Academy of Sciences, 2004)
Nanos (Nos) is one of the evolutionarily conserved proteins known to direct germ-line development. In Drosophila, maternal Nos protein maintains transcriptional quiescence in the germ-line progenitors or pole cells to repress ectopic expression of somatic genes. Here we show that maternal Nos is required to establish and maintain germ-line identity by preventing apoptosis and somatic cell fate. The pole cells lacking maternal Nos were degraded by apoptosis during mid to late embryogenesis. When apoptosis was suppressed by Df(3L)H99, some pole cells lacking Nos adopted somatic cell fates. These pole cells expressed somatic markers ectopically and lost the germ-line marker Vasa. We further found that some Nos-negative pole cells were able to migrate into the gonads, but they failed to develop as functional germ cells during postembryonic stages. We propose a model in which Nos establishes germ-line/soma dichotomy and is also required to maintain germ-line fate.